The public's attitude toward recycled water: a review - Hamza T. Alrikabi; Salah L. Zubaidi (Wasit Journal of Engineering Sciences)
Many locations worldwide are encountering significant obstacles to achieving economic and social sustainability due to the increasing disparity between water availability and demand resulting from population expansion. Therefore, many countries are looking for alternative water sources to increase their water supply. Water reuse has become a practical and effective method for addressing water scarcity. A systematic review and meta-analysis of water reuse are necessary to provide guidance for future studies on the impact of water reuse and to assist managers in optimizing the usage of water reuse technology for improving workplace and organizational results. This is the initial systematic review to investigate the correlation between public acceptance and water reuse. This systematic research aims to provide a comprehensive analysis and summary of public acceptance regarding water reuse surveys. The study compiled data from 85 original research papers published between 2018 and August 1, 2023. The information included details such as keywords, Geographic location, Cloud of words co-occurrence, sample size, publication peer years, published journals, and affiliations. In addition to this, it evaluated potential avenues for future research in this area and offered recommendations for enhancing the public's acceptance of water reuse.